Dampak Pemberian Motivasi, Work Environment Serta Leadership Style Pada Peningkatan Kerja Karyawan PT. Gapura Angkasa Bandara Sultan Hasanuddin Makassar - Haeranah Alwany (MBIA, 2019)
The purpose of this research is to know the influence of giving motivation, work environment and leadership style on performance of employees At PT. Gapura Angkasa in Makassar Hasanuddin International Airport which consists of giving motivation, work environment and leadership style. The population in this case at 54 employees. Methods of data analysis using quantitative with linier regression. Based on a test of the free variabel F jointly have significant and positive influence against variabels bound performance. Through testing (R) correlation coefficient obtained that level of correlation or relationship between giving motivation, work environment and leadership style on performance of employees is a high relationship i.e. 60.8%. And the ability to work is the most dominant factor influencing the performance of employees at PT. Angkasa Gate in Makassar Hasanuddin International Airport.